Medicinal plants of the genus Macleaya (Macleaya cordata, Macleaya microcarpa): A review of their phytochemistry, pharmacology, and toxicology. (12th November 2017) - Lin, Li; Liu, Yan‐Chun; Huang, Jia‐Lu; Liu, Xiu‐Bin; Qing, Zhi‐Xing; Zeng, Jian‐Guo; Liu, Zhao‐Ying
Abstract : In the genus Macleaya, Macleaya cordata and Macleaya microcarpa have been recognized as traditional herbs that are primarily distributed in China, North America, and Europe and have a long history of medicinal usage. These herbs have been long valued and studied for detumescence, detoxification, and insecticidal effect. This review aims to provide comprehensive information on botanical, phytochemical, pharmacological, and toxicological studies on plants in the genus Macleaya . Plants from the genus of Macleaya provide a source of bioactive compounds, primarily alkaloids, with remarkable diversity and complex architectures, thereby having attracted attention from researchers. To date, 291 constituents have been identified and/or isolated from this group. These purified compounds and/or crude extract possess antitumor, anti‐inflammatory, insecticidal, and antibacterial activities in addition to certain potential toxicities. Macleaya species hold potential for medicinal applications. However, despite the pharmacological studies on these plants, the mechanisms underlying the biological activities of active ingredients derived from Macleaya have not been thoroughly elucidated to date. Additionally, there is a need for research focusing on in vivo medical effects of Macleaya compounds and, eventually, for clinical trials.